Evaluation of Factors Affecting the Efficacy of Nitroglycerin Infusion in Patients with Hypertensive Crisis: Effects of nitroglycerin in hypertensive crisis - Khademvatan, Kamal; Gerami, Farzaneh; Abbaszadeh, Samin; Soraya, Hamid (Iranian Journal of Pharmaceutical Sciences, 2021)
Hypertensive crisis is a severe elevation in blood pressure (BP) that requires urgent reduction in BP to prevent or reduce target organ damage. The antihypertensive effects of nitroglycerin have been proven, but there are limited reports on the effects of various factors on the effectiveness of nitroglycerin in the treatment of hypertensive crisis. The purpose of this study was to evaluate the effects of diabetes, history of hypertension and age as well as gender differences in the effectiveness of nitroglycerin in patients with hypertensive crisis. This study included 76 patients with hypertensive crisis. For management, nitroglycerin initially started at 5 μg/min by intravenous infusion and, if needed, every 3 to 5 min, 5 μg/min was added to the above dose to a maximum of 20 μg/min as long as the blood pressure level reaches to the desired level. The results showed that the mean time of reduction of BP to the desired level in patients with history of hypertension and diabetes alone or both diseases, increased significantly in comparison to patients without these underlying diseases (P<0.01, P<0.01 and P<0.05 respectively). The results also demonstrated that there is a significant difference between patients younger than 45 and over 65 years with patients aged 45-65 (P<0.05). There is no difference between two genders in each group (P>0.05). In conclusion, patients with diabetes and/or history of hypertension are more resistant to pressure lowering effect of nitroglycerin in hypertensive crisis. Patients under 45 years of age as well as the elderly are also resistant. Therefore, it is advisable for physicians to choose the appropriate treatment for the desired outcome, considering the patient’s condition.